PEMILIHAN KEPALA DESA DALAM PERSPEKTIF PERTUKARAN SOSIAL (STUDI KASUS PADA PEMILIHAN KEPALA DESA SUMBERARUM 2019 KECAMATAN KEREK KABUPATEN TUBAN) - Ciptono, Ciptono; Pujileksono, Sugeng (Universitas Wijaya Kusuma Surabaya, 2021)
The election of village heads (pilkades) is one of the manifestations of democracy in the village. Pilkades allows every eligible villager to have the right to choose who will lead their village. In practice, the 2019 Pilkades in Sumberarum cannot be separated from various forms of social exchange. The social exchange in question is the exchange between the candidate for the village head and the voters. The aims of this study were (1) to identify the type of social exchange in the Pilkades, (2) to find the elements of social exchange in the Pilkades, (2) to identify the arena of social exchange in the Pilkades, and (3) to identify patterns of social exchange in the Pilkades. This study uses a qualitative approach with case study research methods. The results showed that the social exchange between the candidate for the village head and the voters used the arena of mlawang, jajang, mayoran and dispatch. The types of exchange that occurred included direct exchanges and indirect exchanges. Indirect social exchange, involving botoh, elder figures, village officials and heads of community organizations. In the process of social exchange, it is unavoidable that there is an element of power. The power of the village head candidate comes from material resources, while the power of the voter comes from the ‘vote’ owned by the voters. It is this difference in sources of power that requires both parties to negotiate. This is what causes symmetrical and asymmetrical exchange patterns. The general norm that applies is that voters determine their choice and support for the village head candidate who is considered to provide the most material and non-material rewards.Keywords: power, social exchange, pilkades, exchange pattern, exchange type.